Maslinic acid induces autophagy and ferroptosis via transcriptomic and metabolomic reprogramming in prostate cancer cells - Hu, Fen; Sun, Yuxi; Zhang, Yunfeng; Chen, Jiaxin; Deng, Yingzi; Li, Yifei; Li, Ruobing; Zhang, Juan; Liang, Yongping; Liu, Yan; Wang, Shuqing; Li, Mi; et al. (Frontiers in Pharmacology, 2024)
Prostate cancer has the second highest incidence among male malignancies. Only a few studies exist on the inhibitory effects of maslinic acid (MA) on prostate cancer. Herein we found that MA inhibits prostate cancer cell proliferation by decreasing CDK2, CDK4, and CDK6 expression and concurrently increasing p27, Rb, p-Rb expression. Further, MA was observed to induce prostate cancer cell autophagy by increasing the expression of p53, p-p53, ULK1, Beclin1, Atg7, and Atg5 and the ratio of LC3-II/I and concurrently decreasing the expression of ERK1/2 and mTOR. In addition, MA induced RM-1 cell ferroptosis by regulating glutathione, glutamate, and oxidized glutathione concentrations, inhibiting SLC7A11 activity, and downregulating GPX4 expression. Integrated metabolome and transcriptome analysis led to the identification of key pathways (e.g., pathways in cancer and glutathione metabolism). Real-time quantitative PCR confirmed that MA regulates the expression of ABCA1, JUN, and NFKBIA. In vivo, we demonstrated that 50 mg/kg MA significantly inhibited the growth of tumors established using RM-1 cells. To summarize, we report that MA inhibits prostate cancer cell growth both in vitro and in vivo by inducing autophagy and ferroptosis via transcriptomic and metabolomic reprogramming.